Cost of management of patients with haemophilia. Issue 6033 (21st August 1976) - Carter, F; Forbes, C D; MacFarlane, J D; Prentice, C R
Abstract : The cost of managing 114 adult haemophiliacs in the west of Scotland was assessed for the period 1 March 1971 to 28 February 1974. Altogether 23 of them (20%) accounted for 80% of the resources used. The cost of hospital treatment of these patients during the period was compared with the predicted cost of home treatment, given the availability of freeze-dried factor VIII concentrate in sufficient amounts. We calculate that adequate on-demand home treatment would cost only 16% more than the present treatment, which is substantially less efficient.